Implementation of midwifery continuity of care models for Indigenous women in Australia: Perspectives and reflections for the United Kingdom. (February 2019) - Fernandez Turienzo, C.; Roe, Y.; Rayment-Jones, H.; Kennedy, A.; Forster, D.; Homer, CSE.; McLachlan, H.; Sandall, J.
Abstract: Maternity models that provide midwifery continuity of care have been established to increase access to appropriate services for Indigenous Australian women. Understanding the development and implementation of continuity models for Indigenous women in Australia provides useful insights for the development and implementation of similar models in other contexts such as those for vulnerable and socially disadvantaged women living in the United Kingdom. To ensure better health outcomes for mothers and babies, it is crucial to promote culturally competent and safe public health models in which midwives work collaboratively with the multidisciplinary team.